Lake ANALISIS DINAMIKA LUASAN DANAU DAN TUTUPAN LAHAN SEMPADAN DANAU KERINCI TERHADAP PERILAKU MASYARAKAT DI KABUPATEN KERINCI PROVINSI JAMBI - Dede Purnama Putra (Universitas Negeri Padang, 2021)
This research started from the researcher's observation of the current condition of Lake Kerinci, which has undergone changes in the area of ​​the lake and the conversion of lake border land functions which has led to changes in land cover around the lake. Changes in the area of ​​this lake occur, one of which is a lot of sediment entering the lake, besides that the land cover is always changing due to increased land needs which have an impact on increasing land use changes that occur. This type of research is descriptive quantitative that is by looking for information on existing symptoms. The sampling technique used a stratified random sample of 30 people. Data collection techniques were carried out using primary data and secondary data. Furthermore, the data were analyzed by descriptive analysis techniques and image interpretation spatial analysis techniques. The results of the study conclude that the dynamics of lake area and lake border land cover are quite varied. From 2000 to 2020 the lake is always changing and the types of lake border land cover such as shrubs, swamp scrub, settlements, rice fields and tourist attractions are always changing the area and behavior of the people around the lake to improve the lake just waiting for a policy from the government, people are less enthusiastic about change what happened to the lake